THE PHYSICAL PARAMETERS OF THE GAS AND DUST IN COMETARY ATMOSPHERES - Churyumov, K. I.; Ponomarenko, V. O.; Kleschonok, V. V. (Одеські астрономічні публікації, 2016)
The results of observations and studies of comets on the basis of the optical spectra with an average resolution were presented. Spectral material was mainly produced in 2009–2012 with the help 2-m telescope Zeiss (F1 = 6.3 m; F2 = 16 m) at high mountain astronomical station "Terskol" of Main Astronomical Observatory of National Academy of Sciences of Ukraine and the Institute of Astronomy RAS. The resolution of the spectra R ≈ 1500, R ≈ 4500, R ≈ 14000; wavelength ranges λλ = 3850–8000 ÅÅ. Using the spectra of comets, based on the model Hazer, was performed the following work: carried out the identification of spectral emission lines, obtained physical parameters of the neutral gas atmosphere of comets. And also, physical parameters the dusty atmosphere.